Spatial diversity patterns of understory shrub community in Srengseng urban forest, Jakarta - Gabriella Ria Kirana; Erwin Nurdin; Wisnu Wardhana; Adi Basukriadi; Andriwibowo Andriwibowo (Foresty Faculty of Hasanuddin University, 2023)
Urban forests are one of the natural ecosystems in urban environments. One of the most important components of the urban forest ecosystem is the understory shrubs. Therefore, this study aims to estimate the diversity of understory shrubs in the Srengseng Urban Forest in Jakarta City. The biodiversity of understory shrubs is calculated using the Shannon-Wiener diversity index (H') and mapped using the Geographic Information System (GIS). In this study, 24 plots measuring 2 m by 2 m each were placed to survey the understory shrubs. In total, there were 20 species of shrubs identified, which belong to 12 families with average values of H' is 0.671. The results show that almost 62.78% of the total Srengseng Urban Forest area has a H' diversity range of 1.001–1.500. In comparison, 8.62% of total urban forest area has an H' diversity range of 0.501-1.000. The area of urban forest with the lowest diversity in the H' diversity range of 0.000 to 0.500 reaches 28.58%. The eastern parts of the urban forest have the highest H' in comparison to the other parts of the forest. This study contributes to the conservation and forestry management of forest at an urban scale by identifying parts of the urban forest that should be conserved in the Srengseng. To conclude, the eastern parts of Srengseng Urban Forest sizing 64,765 m2 should be prioritized for understory shrub conservation.